A modified fuzzy TOPSIS approach for the condition assessment of existing bridges - Qu Bing; Lin Shiwei; Huang Haisheng (Nonlinear Engineering)
Bridge condition assessment is a crucial component of bridge management. To better adapt to the multi-level, nonlinear, and multi-criteria decision-making problems in bridge assessments, a modified technique for order preference by similarity to ideal solution (TOPSIS)-based nonlinear method is proposed in a fuzzy environment. First, quantitative representations of three different types of bottom indices of bridge assessment models under the analytic hierarchy process framework are developed using fuzzy numbers. Subsequently, with regard to the conventional TOPSIS approach, several enhancement and optimizations are considered, including the absolutization and fuzzification of positive and negative ideal solutions, the determination of variable weights of bottom-level indexes, fuzzy assessment based on level sets, and the defuzzification and grading of the evaluation results. These measures reduce the ambiguities and uncertainties associated with the conventional TOPSIS approach and can optimally accommodate bridge performance evaluation in fuzzy logic. Finally, to illustrate the practicality and feasibility of the developing method, a real bridge assessment scenario is built. The results indicate that this approach can effectively reflect the real state of the overall bridge, providing a robust basis for bridge maintenance and rehabilitation decision-making.